Policy Design for Guidance and Development of Micro, Small and Medium Industries in Lubuklinggau City - Khalid Haikal Hosali, Muhammad; Yogopriyatno, Jatmiko; Aziz Zulhakim, Abdul (Future Science, 2024)
This paper aims to describe the challenges and proposed strategies and policies for the Development of Micro, Small and Medium Industries in Lubuklinggau City. This research design is descriptive qualitative, data collection is done through four steps namely; observation, semi-structured interviews, documentation and conducting FGDs. Data analysis consists of two main sub-processes: (1) data reduction and pattern identification, and (2) conclusion drawing and conclusion presentation. The results of the study concluded that there are challenges faced in the activities of Guidance and Development of Micro, Small and Medium Industries in Lubuklinggau City to develop five leading sectors namely; wholesale and retail trade sector, transportation and trade sector, accommodation and eating and drinking sector, real estate sector, corporate services sector, and health services sector. Pentahelix Model Design was designed by the Lubuklinggau City Government to organize the Guidance and Development of Micro, Small and Medium Industries by involving five elements namely academics, business, community, government, and media.